Comparative Transcriptome Analysis of the Heat Stress Response in Monochamus alternatus Hope (Coleoptera: Cerambycidae) - Li, Hui; Zhao, Xinyi; Qiao, Heng; He, Xuanyu; Tan, Jiajin; Hao, Dejun (Frontiers in Physiology, 2020)
Temperature is a critical factor of insect population abundance and distribution. Monochamus alternatus Hope (Coleoptera: Cerambycidae) is a significant concern since it is transmitted vector of the pinewood nematode posing enormous economic and environmental losses. This pest shows tolerance to heat stress, especially extremely high temperatures. Exposing for 6, 12, 24, 48, or 96 h, the 50% median lethal temperatures (Ltem50) for fourth-instar larvae were 47.5, 45.5, 43.9, 43.4, and 42.3°C, respectively. A total of 63,360 unigenes were obtained from complementary DNA libraries of M. alternatus fourth-instar larvae (kept at 25°C and exposed to 40°C for 3 h) and annotated with six databases. Five hundred sixty-one genes were significantly upregulated, and 245 genes were downregulated after heat stress. The Gene Ontology enrichment analysis showed that most different expression genes are categorized into “protein folding” and “unfold protein binding” terms. In addition, “Longevity regulating pathway-multiple species,” “Antigen processing and presentation” as well as “MAPK signaling pathway” were significantly enriched Kyoto Encyclopedia of Genes and Genomes pathways. Further analysis of different expression genes showed that metabolism processes were suppressed, while ubiquitin proteolytic system, heat shock proteins, immune response, superoxide dismutase, cytochrome P450s, and aldehyde dehydrogenase were induced after heat shock. The stress signaling transduction pathways such as MAPK, Hippo, and JAK-STAT might be central convergence points in M. alternatus heat tolerance mechanism. The expression levels from quantitative real-time PCR of 13 randomly selected genes were consistent with the transcriptome results. These results showed that M. alternatus possessed strong heat tolerance and genes related to protein activity, immune response, and signal transduction composed of a complicated heat tolerance mechanism of M. alternatus. This research provided new insights into the mechanisms of thermal tolerance in other insects and aided in exploring the function of heat resistance-related genes.